2015
DOI: 10.1007/s00253-015-7063-6
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan removal in wetlands constructed with different aquatic plants

Abstract: Triclosan (TCS) is widely used in consumer products as an antimicrobial agent. Constructed wetlands have the potential for TCS removal, but knowledge about the relative importance of sediment, plants, and microbes is limited. TCS removal performance was investigated in well-operated constructed wetlands planted with three different types of aquatic plants: emergent Cattail (C-T), submerged Hornwort (H-T), and floating Lemnaminor (L-T). Results showed that the TCS removal efficiencies from water were all greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…reported that the diversity and richness of bacteria in planted beds was higher than that in unplanted beds. In addition, Liu et al 22. showed that the root systems of aquatic plants (emergent cattail, submerged hornwort, and floating Lemna minor ) have selective effects on the microbial communities in wetlands, and wetlands with Cattail showed the highest community richness and diversity.…”
Section: Discussionmentioning
confidence: 99%
“…reported that the diversity and richness of bacteria in planted beds was higher than that in unplanted beds. In addition, Liu et al 22. showed that the root systems of aquatic plants (emergent cattail, submerged hornwort, and floating Lemna minor ) have selective effects on the microbial communities in wetlands, and wetlands with Cattail showed the highest community richness and diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of triclosan from the soil pots in the present study may also have been the result of microbial degradation. In 1 study conducted by Liu et al on the potential for constructed wetlands to remove triclosan, results suggested that an abundance of alpha‐ and gamma‐ Proteobacteria could be important in the microbial degradation of triclosan. Furthermore, the extent to which triclosan is available for plant uptake may have also been affected by its half‐life, which ranges from 12.7 d to 83 d in soil (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…qPCR was conducted using the method described by Liu et al to obtain the absolute abundance of bacterial 16S rRNA. The PCR temperature program was as follows: Pre‐heating at 50 °C for 2 min, pre‐denaturation at 95 °C for 10 min, denaturation at 95 °C for 15 s, annealing at 60 °C for 1 min, and extension at 72 °C for 1 min.…”
Section: Methodsmentioning
confidence: 99%